2013
DOI: 10.1038/ajg.2013.110
|View full text |Cite
|
Sign up to set email alerts
|

Mortality Risk According to Different Clinical Characteristics of First Episode of Liver Decompensation in Cirrhotic Patients: A Nationwide, Prospective, 3-Year Follow-Up Study in Italy

Abstract: The occurrence of decompensation marks a crucial turning point in the course of cirrhosis. The purpose of this study was to assess the risk of mortality according to the clinical characteristics of fi rst decompensation, considering also the impact of acute-on-chronic liver failure (AoCLF). METHODS:We conducted a prospective nationwide inception cohort study in Italy. Decompensation was defi ned by the presence of ascites, either overt or detected by ultrasonography (UD), gastroesophageal variceal bleeding (GE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 37 publications
4
31
0
1
Order By: Relevance
“…These results were expected as the EASL‐CLIF Consortium definition of ACLF was based on variables classically related to prognosis in cirrhotics and non‐cirrhotics patients, and was developed with very restrictive thresholds for diagnosis of organ failure . Ascites is also an important prognostic marker in cirrhosis and in the context of acute decompensation is probably an indicator of more advanced liver disease . Supporting our findings, the CANONIC study showed that ascites at enrolment was a risk factor for post‐enrolment development of ACLF , probably reflecting the close relationship between the presence of ascites and the risk of renal failure in cirrhosis .…”
Section: Discussionsupporting
confidence: 86%
“…These results were expected as the EASL‐CLIF Consortium definition of ACLF was based on variables classically related to prognosis in cirrhotics and non‐cirrhotics patients, and was developed with very restrictive thresholds for diagnosis of organ failure . Ascites is also an important prognostic marker in cirrhosis and in the context of acute decompensation is probably an indicator of more advanced liver disease . Supporting our findings, the CANONIC study showed that ascites at enrolment was a risk factor for post‐enrolment development of ACLF , probably reflecting the close relationship between the presence of ascites and the risk of renal failure in cirrhosis .…”
Section: Discussionsupporting
confidence: 86%
“…Non‐hepatic insults were classified as acute precipitating events only after hepatic acute events had been excluded. Overt ascites was diagnosed by clinical examination and ultrasonography as previously described . HE was defined as an episode of neurological and neuropsychiatric abnormality …”
Section: Methodsmentioning
confidence: 99%
“…As already mentioned, the recent Baveno workshop stated that prevention of decompensation is probably more appropriate as an end-point in this group as well, since bleeding is not the most frequent decompensating event (it is usually ascites) and patients with varices are more likely to decompensate than those without varices 22 . Considering only the bleeding episodes as relevant outcomes ignores the profound impact that developing ascites or encephalopathy before bleeding has on the prognosis of cirrhosis 12, 23, 24 . This new approach implies that treatments for this stage should be able to prevent all complications of portal hypertension.…”
Section: Clinical Settingsmentioning
confidence: 99%